The Implementation of Project Based Learning to Improve Students Writing Skill - Elisabeth Z. Oroh; Blessy Monique Wilar (Journal of English Language Teaching, Literature and Culture, 2022)
The aim of this study to improve students writing skill especially for students in SMA Negeri 2 Manado X Ipa 1 The subject of this study is the 36 students in X Ipa 1 SMA Negeri 2 Manado < span>Utilized data collection techniques include observation testing and documentation The first cycle of students learning describes a tourist destination Students have challenges in verbal and non linguistic domains courage honesty and attitude respectively On the second cycle they describe a destination for tourists Cycle II focuses more on linguistic vocabulary structure and punctuation and non linguistic fluency and mastery of language qualities that are still deficient Planning assessment implementation evaluation and project evaluation contain organization vocabulary grammar and mechanics were deemed adequate for this study The results of a test measuring kids writing skills indicate an increase The increase occurred as follows: 1 the average pre cycle value of 72 75 increased to 78 06; 2 the average evaluation value of the first cycle was 78 06 with a completeness percentage of 50 percent; and 3 the average evaluation value of the second cycle is 84 46 with a completeness percentage of 84 37 percent < span>< p>